2016
DOI: 10.1186/s12906-016-1474-5
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on the therapeutic effect of propolis along with standard antibacterial drug in Salmonella enterica serovar Typhimurium infected BALB/c mice

Abstract: BackgroundAntibiotic resistance is an emerging public health problem. Centers for Disease Control and Prevention (CDC) has described antibiotic resistance as one of the world’s most pressing health problems in 21st century. WHO rated antibiotic resistance as “one of the three greatest threats to human health”. One important strategy employed to overcome this resistance is the use of combination of drugs. Many plants, natural extracts have been shown to exhibit synergistic response with standard drugs against m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…The mutation and deletion of Nramp1 gene cause mice to be susceptible to many diseases [10]. Preeti Kalia et al reported that BALB/c mice infected by S. typhimurium MTCC98 manifested high temperature, loose coat, sleepiness, and other typical typhoid symptoms; therefore, this mouse model was used for the study of the efficacy of combined treatment of Propolis and Cefixime [11]. In our study, the BALB/c mice were used.…”
Section: Introductionmentioning
confidence: 98%
“…The mutation and deletion of Nramp1 gene cause mice to be susceptible to many diseases [10]. Preeti Kalia et al reported that BALB/c mice infected by S. typhimurium MTCC98 manifested high temperature, loose coat, sleepiness, and other typical typhoid symptoms; therefore, this mouse model was used for the study of the efficacy of combined treatment of Propolis and Cefixime [11]. In our study, the BALB/c mice were used.…”
Section: Introductionmentioning
confidence: 98%
“…Bulgarian propolis showed synergistic effect when combined with chloramphenicol, tetracycline and neomycin, and has proven effective for the treatment of Salmonella typhi infection [14]. Synergistic interactions between propolis and several antibiotics including streptomycin, cloxacillin and cefixime have also been reported [15, 16]. Malaysian propolis nanoformulation with chitosan has been reported to be effective against Enterococcus faecalis biofilms [17].…”
Section: Introductionmentioning
confidence: 99%
“…The safety of propolis is secured not only by its long history of usage as a folk medicine but by in vitro and in vivo safety assessment studies (Burdock 1998; Sforcin 2016). Propolis has antibacterial activity against a range of pathogens (Wojtyczka et al 2013; Kalia et al 2016), including in vitro antibacterial activity against periodontopathic bacteria (Santos et al 2002), and it improves microbiological and clinical parameters in periodontal tissues (Coutinho 2012; Sanghani et al 2014). Recent advances in separation and identification techniques revealed a range of chemical compounds in propolis, including flavonoids, terpenoids, and phenolics (Huang et al 2014).…”
Section: Introductionmentioning
confidence: 99%